Morphological and Chemical Effects of Plasma Treatment with Oxygen (O-2) and Sulfur Hexafluoride (SF6) on Cellulose Surface - Gonzaga de Camargo, Janine Sanches [UNESP]; Menezes, Aparecido Junior de; Cruz, Nilson Cristino da [UNESP]; Rangel, Elidiane Cipriano [UNESP]; Delgado-Silva, Adrian de Oliveira (Univ Fed Sao Carlos, Dept Engenharia Materials, 2017)
Cellulose is a polymer widely available in nature, however its applications may be restrict due to its hydrophilic character. The creation of hierarchical structures on the surface is one of the required factors to obtain the hydrophobicity of this material. In order to compare the morphological and chemical effects caused by the action of different gases in the creation of nanostructures on the cellulose surface, samples were exposed to oxygen (O-2) and sulfur hexafluoride (SF6) plasma treatments. The changes in morphology after treatment prove that both the gases were able to create similar nanostructures in the material. The analysis of elemental composition and identification of functional groups on the sample surface showed that chemical modifications occurred differently for each treatment. Contact angle measurements revealed that samples treated by O-2 plasma remained hydrophilic, whereas low receptivity to polar (theta > 120 degrees) and non- polar (theta > 100 degrees) liquids was observed for samples exposed to SF6 plasma.
Keywords: cellulose; plasma treatment; hydrophobicity; hierarchical structures